Intraocular medulloepithelioma: an unusual and challenging entity in paediatric population - Uzma Imam; Marya Hameed; Anis, Irma; Israr Bhutto; Syed Habib Ahmed; Attiya Rizvi; Zubair Ahmad (Journal of the Pakistan Medical Association, 2023)
Intraocular medulloepithelioma is a rare, congenital tumour of the non-pigmented ciliary epithelium. It most frequently arises from the ciliary body but can also have its origin from the retina, iris and optic nerve. The age when lesion first appears is typically around 2-10 years. Nearly 50-60% of patients having this lesion may also have secondary features such as cataract and neovascular glaucoma. Those with extrascleral medulloepithelioma are at risk for metastasis. Systemic correlation of the tumour with pleuropulmonary blastoma/DICER1 gene is reported in the literature. Here, we report a case of a 15 years old boy with one year history of right eye proptosis and painful red right eye along with decreased vision for one week. He was assessed and operated for cataract elsewhere three years back. ---Continue